Improvement Efforts Indonesian Language Literacy - Anita Candra Dewi; Suarli; Ummu Kalsum; Mawar Saputri; Trisnadia; Nur Annisa Syarbiah (International Journal of Educational and Psychological Sciences, 2023)
The Literacy Movement is aparticipatory activity in volving all school members (learners, teachers, principals, education personnel, school supervisors, school committees,andparents) This is related to the learning carried out in schools that Literacy is synonymous with reading and writing activities including how a person communicates insociety. Literacy also means social practices and relation ships related to knowledge, language and culture (UNESCO, 2003). Students' abilities as learning subjects in the School Literacy Movement in clued the ability to determine, identify, find, evaluate, create information in an organized manner in order to communicate it to each individual to actively participate in learning at school an dinsociety. Currently, the meaning of literacy has developed, which includes various fields of knowledge used. There are several components of literacy (Suragangga, 2017), namely early literacy, basic, library, media, technology, andvisual. Early literacy is a listening competency by understanding the use of spoken language in the environment Basic literacy in cludes Indonesian language competencies (listening, reading, speaking and writing), counting, and critical thinking.